Nourishing island food systems in Solomon Islands: Operational Plan 2023 - Eriksson, Hampus; Aropa, Aloysius; Batalofo, Margaret; Notere Boso, Delvene; Gomese, Chelcia; Harohau, Daykin; Hunnam, Kimberly; Leinga, G; Orirana, Grace; Pua'ara, S; Ride, Anouk; Saeni-Oeta, Janet; et al. (WorldFish, 2023)
The WorldFish program in Solomon Islands is organized around four main research pathways (see figure). The first three are the agreed-upon impact areas of WorldFish, which aligns toward our adopted goal from the Solomon Islands National Fisheries Policy 2019–2029 of the Ministry of Fisheries and Marine Resources (MFMR). The fourth research pathway places a deliberate emphasis on integrated planning and partnerships. Although WorldFish in Solomon Islands has many partners, we particularly integrate our research with MFMR to support national strategies toward its policy goal.